Effect of Adding Zirconia and Alumina Nanoparticles on the Tensile and Flexural Properties of Polymer Blend Based on Polypropylene - Teeb Adnan Mohameed (Journal of Global Pharma Technology, 2020)
Polypropylene is an important material used in many structural applications, including automotive and aircraft parts as well as machine parts. In this paper, the properties of polypropylene were improved by blending it with 5% ratio of poly methyl methacrylate (PMMA) and adding nanoparticles powders of zirconia (ZrO2) and alumina (Al2O3) in different ratios (0.3, 0.5 and 0.7%) to polymer blend, which consists of [PP: 5% PMMA and adding 1% of (polypropylene-grafted-malic anhydrated (PP-g-MA) as compatibilizing agent)]. Polymer blend and its nanocomposites were prepared by melt blending technique using twin screw extruder. Investigation of some mechanical properties and the morphology structure test of the nanocomposites samples was studied. The results illustrated that the mechanical properties increased when adding nanoparticle (ZrO2 and Al2O3) to polymer blend (PP: 5%PMMA: 1%(PP-g-MA)) and the highest values were obtained for tensile strength, modulus of elasticity, flexural strength and flexural modulus, at 0.3% ratio of (ZrO2 and Al2O3) nanoparticles in the blend. The fracture surface morphology showed that the addition of nanoparticles led to reduce the micro pores that exist in the morphology structure of polymer blend.Keywords: Polymer blend, Nanocomposite, PP, PMMA.